Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Hasil Belajar Siswa Materi Asam-Basa Menggunakan Alat dan Bahan di Lingkungan Sekitar di Kelas XI MIA SMA Negeri 1 Tombatu - Brian Pontoh; Ignatius R. S. Santoso; Hardin F. Rares (Chemistry Department, Universitas Negeri Manado, 2022)
This study aims to determine the effect of the application of the think pair and share model learning on acid-base material using surrounding materials and tools on student learning outcomes in the experimental class and control class XI Mia SMA N 1 Tombatu. The research sample was students of class XI Mia 1 and XI Mia 2. The results showed that there were differences in student learning outcomes in the experimental class compared to students in the control class who used conventional learning models. Where the average student learning outcomes Experiment class is 81.6 and the average student learning outcomes Control class is 73.9. It can be concluded that the Think Pair and Share (TPS) model of cooperative learning has an influence on the learning outcomes of experimental and control students on acid-base material. Therefore, it can be suggested that the Think Pair and Share (TPS) model of active learning activates students in the learning process in order to improve student learning outcomes.